Aspectos psicológicos del comportamiento humano en la productividad de la empresa en el Ecuador: una aproximación desde la medicina del trabajo - Cánchig Loya, Juan Carlos (2017)
Purpose: faced with the demands of productivity in companies, the group and individual interaction of the human being is yielding results that are immersed in occupational medicine; Therefore the objective is to validate a methodology that determines the psychological aspects of human behavior through the application of recognized psychosocial assessments to determine their impact on the productivity of the Ecuadorian company.Material and methods: the research starts from psychosocial studies (Fpsico and ITSAS 21), analyzes the processes, financial results of the company and proposes prevention measures. Observation, interview, survey and psychological reagents were used.Results: risk factors evaluated by FPSICO were time of work, autonomy, workload, psychological demands, variety / content of work, supervision / participation, worker interest / compensation, role performance,relationships and social support. The ISTAS 21 method considered factors of psychological demands, control over work, insecurity about the future, social support and quality of leadership, double presence and esteem.Conclusion: the methodology validated in the investigation determined that the psychological aspects of human behavior influence the productivity of the company; Being able to be identified through psisocial studies and, of course, its success depends directly on the application of the primary prevention recommendations (work organization), secondary (individuals) and tertiary (recovery and rehabilitation of people) recommendations according to the aspect found